FENOMENA KINERJA BIROKRASI PEMERINTAH: Studi Kasus di Dinas Pendidikan kabupaten Sukabumi - Encep Solihutaufa (STISIP Widyapuri Mandiri Sukabumi, 2022)
The purpose of this study was to determine the performance of the government bureaucracy, especially with regard to organizational efficiency, teamwork, and the relationship between leaders and subordinates at the Dinas Pendidikan in Kabupaten Sukabumi, the factors that support and hinder the performance of the government bureaucracy, especially with regard to service efficiency, teamwork, and leadership relationships. with subordinates. The research method used is descriptive, which is a study that describes the performance of the government bureaucracy from the point of view of the process approach by determining the descriptive variables, namely; service efficiency, teamwork, and leadership relationships with subordinates. The results of the research are the level of performance of the Dinas Pendidikan Kabupaten Sukabumi in carrying out the function is in a moderate level of performance, the organizational efficiency of the Dinas Pendidikan Kabupaten Sukabumi in achieving the function of education management is in a good level. Judging from the time indicator used in the implementation of services in the field of education. Judging from the cost indicators used, which are still low compared to the existing needs. Likewise, the employees used for the implementation of educational development services are inadequate compared to the needs required. The performance of the Dinas Pendidikan Kabupaten Sukabumi in building excellent teamwork to carry out the main tasks and functions of the service is formed on the basis of mutual trust, mutual respect and complementarity among all elements and layers of service. This can be seen from the results of research which shows that the teamwork created by the Dinas Pendidikan Kabupaten Sukabumi is at a moderate level.